(untitled) (American Journal of Islam and Society, 2005)
The expanding Muslim communities in Western Europe have become a source of consternation in European capitals. Central to the issue of Europe’s growing Muslim population is how far the secular state is willing to accommodate religious practices deemed to be antithetical to “European” values. Fetzer and Soper’s timely comparative study effectively addresses the issue’s historical foundations as well as clearly explains the European Muslims’ disparate political responses. The authors’ central focus is how three core European states have accommodated the needs of Muslims flooding their borders since the 1960s. Exploring Europe’s surprisingly disjointed response to Muslim immigration proves to be both theoretically interesting and an invaluable exercise in debating what options are available to elected governments that are being increasingly pressured by right-wing activism when it comes to accommodate the practice of Islam in Europe. The questions raised in the book’s six chapters, three of which are dedicated to the countries in question and the others to presenting the data collected via the authors’ surveys, should prove helpful to larger discussions in European studies about what the contemporary dilemmas facing Germany, Britain, and France are in the context of the so-called war on terrorism. While most studies on Islam in Europe, particularly migration and gender studies, focus on how Muslims mobilize their socioeconomic resources, Fetzer and Soper contend that developing a public policy on Muslim religious (and political) rights is actually mediated in significant ways by the different institutional church/state patterns within each country. This move away from the assumption that Muslims, if organized in the right way, could expect certain institutional concessions in “democratic Europe” proves to be a helpful intervention into a sometimes doctrinally ...